Una nueva interpretación de El casamiento de Witold Gombrowicz a la luz de la traducción de la obra al castellano realizada por el propio autor - Zaboklicka Zakwaska, Bożena Anna (Eslavística Complutense, 2007)
Gombrowicz is the author of the Spanish versions of his two masterpieces originally written in Polish: Ferdydurke and The marriage. The comparison between his Spanish version of The marriage and the Polish original let us discover important diferences in the structure of the text, differences that suggest the possibility of interpreting this drama of the form as an “exterior drama” in opposition to the generalized opinion of the Polish investigators that tend to define it as an “interior drama”.